2016
DOI: 10.1016/j.jcrs.2016.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Myopic laser in situ keratomileusis retreatment: Incidence and associations

Abstract: None of the authors has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 7 publications
5
22
0
1
Order By: Relevance
“…Previous reports [2,5,36] indicated that older-aged patients are more likely to develop regression or require retreatment, as was found in the multivariate analysis in our study. One explanation is that surgeons are careful to undercorrect with myopic presbyopia with patients who are around 40 years of age, while they tend to overcorrect for young patients [41].…”
Section: Agesupporting
confidence: 87%
See 2 more Smart Citations
“…Previous reports [2,5,36] indicated that older-aged patients are more likely to develop regression or require retreatment, as was found in the multivariate analysis in our study. One explanation is that surgeons are careful to undercorrect with myopic presbyopia with patients who are around 40 years of age, while they tend to overcorrect for young patients [41].…”
Section: Agesupporting
confidence: 87%
“…Rao et al [35] reported greater undercorrection in eyes with preoperative keratometry readings of \ 43.5D than those with preoperative readings of [ 44.5D. However, Russell et al [36] found that higher K power (mean K) significantly increased the odds for regression and retreatment, because steep corneas were less stable, and therefore, they regressed more and might be corneal ectasia.…”
Section: Pre-k Maxmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the immense advances in RS over the last few decades and the stringent criteria for safety, efficacy, costeffectiveness, and predictability of the refractive outcome [5,6] that have been introduced, a small but not negligible percentage of RS outcomes require corrective retreatment [7][8][9]. Although the incidence of RS failures in certain clinics has declined (2-year annual retreatment rates) from 4.52% for primary surgeries done in 2005 to 0.18% for surgeries performed in 2012 [18] and, generally, is extremely low there is still room for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The methods for the individualized correction of refractive errors and the techniques that are presently available fulfill stringent criteria for safety, efficacy, cost-effectiveness, and predictability of the refractive outcome [5,6]. However, a small but not negligible percentage of RS outcomes require corrective retreatment [7][8][9]. Despite the small incidence of RS failures, it is extremely important that they are minimized.…”
Section: Introductionmentioning
confidence: 99%